VACTERL Sendromu ve Anestezi - Je, Paz; Vacterl, Castille Ee; Ün, Basaran; Güzel, A.; Ba, Dean; Wr, Richard (Harran Üniversitesi, 2012)
VACTERL'li hastada anestezi yönetimi prematürite, aspirasyon riski, endotrakeal tüpün fistül içine yerleştirilmesi mide perforasyonu ve efektif olmayan havalanma riski ve eşlik eden anomaliler nedeniyle dikkatli bir şekilde yürütülmelidir. Bu makalede, anorektal malformasyon nedeniyle operasyona alınan VACTERL'li bir olgu sunulmuştur

The management of anesthesia in a patient with VACTERL anomaly has to be taken some concerns with regard to prematurity, risk of aspiration, the misplacement of the endotracheal tube into the fistula thereby raising the risk of gastric perforation and ineffective ventilation , and another coexisting anomalies. In this case we presented a patient with VACTERL and planned for surgery for anorectal malformation
VACTERL Syndrome and Anesthesia